Pengaruh latihan cross country terhadap peningkatan V02max dan kecepatan pada atlit pencak silat di perguruaan bakti negara kabupaten lombok utara tahun 2024 - Muhsan; Ni Ketut Swartini; Dadang Warta Candra Wira Kusuma (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aims to determine the effect of cross country training on improving VO₂max and speed in pencak silat athletes of Perguruan Bakti Negara, North Lombok Regency in 2024. The research method used was a quasi-experimental design with a one-group pre-test and post-test approach. The population consisted of 30 athletes, and the sampling technique used was random sampling. The instruments used were the bleep test to measure VO₂max and a 30-meter sprint test to measure speed. Data analysis was conducted using normality tests, homogeneity tests, and paired sample t-tests with the assistance of SPSS 27. The results showed an increase in the average VO₂max and speed values after the cross country training treatment. The hypothesis test results indicated a significance value (2-tailed) of 0.000 < 0.05, meaning there was a significant difference between pre-test and post-test results. Therefore, it can be concluded that cross country training has a significant effect on improving VO₂max and speed in pencak silat athletes.